The American question [videorecording (DVD)] - Seeman, Guy; Kicklighter, James; Chua, Amy; Woodard, Colin, 1968-; Mounk, Yascha, 1982- (Gravitas Ventures, 2024)
The American Question examines the insidious roots of American polarization in a desperate search for a path forward. Guided by an all-star lineup of experts, explore how the problems plaguing society today are all intertwined.